Are imports of illegal timber in China, India, Japan and South Korea considerable? based on a historic trade balance analysis method. (1st October 2020) - Guan, Zhijie; Chen, Xiaoyu; Xu, Yan; Liu, Yaofei
ABSTRACT: Illegal logging has caused serious damage to the global forest environment. China, Japan, India and South Korea have been criticized for their imports of illegal timber. Based on a trade balance analysis method, this paper evaluates the imports of illegal timber of China, Japan, India and South Korea. The results show that China has serious illegal timber imports with the Republic of Congo, Ghana, Papua New Guinea, Laos, Brazil and Malaysia. India has serious illegal timber imports with Brazil and Papua New Guinea. Japan has serious illegal timber imports with the Republic of the Congo, Cameroon, Malaysia and Papua New Guinea. South Korea has serious illegal timber imports with Malaysia. In order to control the imports of illegal timber, there is a need to further strengthen international cooperation and domestic legislation, enhance the protection and cultivation of forest resources and reduce dependence on imported timber.